UJI DAYA HAMBAT DAUN SENGGANI (Melastoma malabathricum L.) TERHADAP Trichophyton mentagrophytees DAN Candida albicans - Gholib, Djaenudin (BERITA BIOLOGI, 2009)
The in vitro study of" inhibition effect of senggani leaves (Melastoma malabathricum L.) ethanol extract on Trichophyton mentagrophytees and Candida albicans was conducted by diffusion and dilution method. The extract was diluted into 5%, 10%,15% and 20% for diffusion test, and 1%, 2%, 3%, 4% and 5% for dilution test on T. mentagrophytees, and 2%, 4%, 6%, 8%, and 10% on C. albicans. The results showed that the extract inhibited fungal growth. Agar diffusion test (agar wheel) was observed by diameter of inhibition zone around the wheel. At 20% extract dilution, the diameter mean was estimated 30 mm on T. mentagrophytees, and 21 mm on C. albicans. In dilution test, the result showed Minimal Inhibition Concentration (MIC) of the extract was 3% on T. mentagrophytees, and 6% on C. albicans. It is concluded that the extract effect of inhibition on T. mentagrophytees is greater than that on C. albicans.